Emotional, Behavioral and Cognitive Engagement in Language Learning: The Experience of the Successful Learners - Maru, Mister Gidion; Pajow, Christin Natalia (Celt: A Journal of Culture, English Language Teaching & Literature, 2019)
This study aims at investigating and portraying learners’ engagement with language in the learning process. It further shares the influence of the engagement upon the success of language acquisition. This study is methodologically qualitative. The semi-structured interview is implemented based upon the attempts to elaborate seven main questions and several follow-up questions. The respondents are from Manado, North Sulawesi. They are learners whose score above 500 in TOEFL ITP or equivalence to IELTS above 6.0 as the qualification of successful English language learners. They took the test in different institutions such as the Golden Gate and the British Council. The data are then analyzed and interpreted in triangulation. The research findings showed that the engagement has shaped the success of the learners’ language acquisition. The engagement comes in the forms of emotional, behavioral and cognitive ones. Such engagements take place from the silent period to communicative competence period of acquisition. It is further found out that to ensure the success of language acquisition, the three models of engagement have to be persistently and consistently practiced and developed.